A cytotoxic peptide-drug conjugate for tumor-specific delivery of co-injected molecules - Norio Miyamura; Chisato M. Yamazaki; Yasuaki Anami; Kyoji Tsuchikama; Kazuki N. Sugahara (PLoS ONE, 2025)
An ideal cancer therapy enhances anti-tumor effects while minimizing side effects. iRGD, a non-cytotoxic peptide that activates a tumor-specific molecular transport machinery, promotes the penetration of co-injected drugs into tumor tissues. Clinical trials have demonstrated its potential as a tumor-specific delivery scaffold and potentiator of anti-cancer agents. In this study, we synthesized an iRGD conjugate containing monomethyl auristatin F (MMAF), a highly toxic antimitotic agent, and characterized its dual function as a tumor-specific cytotoxic agent and co-injected drug delivery scaffold. The iRGD-MMAF conjugate internalized and killed cultured tumor cells in an αv integrin-dependent manner. When injected systemically, iRGD-MMAF homed selectively to tumors in mice, and extensively spread in the extravascular tumor tissue in line with the tumor-penetrating capacity of iRGD. iRGD-MMAF also significantly enhanced tumor-specific entry of a co-injected molecule by serving as an effective drug delivery scaffold. The results indicate that a chemically modified iRGD peptide with an added therapeutic benefit retains its ability to deliver co-injected agents to tumors.